Efficacy of Magnifying Endoscopy with Narrow-Band Imaging in the Diagnosis of Early Gastric Cancer and Gastric Intraepithelial Neoplasia - Zhu, Yanan; Wu, Kejian; Wang, Fang Yu (Turkish Journal of Gastroenterology, 2024)
Background/Aims: Early diagnosis of gastric cancer can improve the prognosis of patients, especially for those with early gastric cancer (EGC), but only 15% of patients, or less, are diagnosed with EGC and precancerous lesions. Magnifying endoscopy with narrow-band imaging (ME-NBI) can improve diagnostic accuracy. We assess the efficacy of ME-NBI in diagnosing ECG and precancerous lesions, especially some characteristics under NBI+ME. Materials and Methods: This was a retrospective analysis of 131 patients with EGC or gastric intraepithelial neoplasia (IN) who had undergone endoscopic submucosal dissection and were pathologically diagnosed with EGC or IN according to 2019 WHO criteria for gastrointestinal tract tumors. We studied the characteristics of lesions under ME-NBI ,compared the diagnostic efficacy of ME-NBI and white light endoscopy (WLI) plus biopsy, and investigated the effect of Helicobacter pylori infection on microvascular and microsurface pattern. Results: The diagnostic accuracy of ME-NBI for EGC, high-grade IN (HGIN), and low-grade IN (LGIN) was 76.06%, 77.96%, and 77.06%, respectively. The accuracy of WLI plus biopsy in diagnosing the above lesions was 69.7%, 57.5%, and 60.53%, respectively. The rate of gyrus-like tubular pattern was highest in LGIN (60.46%), whereas the highest rate of papillary pattern was 57.14% in HGIN and villous tubular pattern was 52% in EGC. Demarcation lines have better sensitivity for differentiating EGC from IN (92.06%). Conclusion: The ME-NBI has higher diagnostic accuracy for EGC than WLI plus biopsy. Demarcation lines and villous and papillary-like microsurface patterns are more specific as EGC and HGIN characteristics. The cerebral gyrus-like microsurface pattern is more specific for LGIN. Cite this article as: Zhu Y, Wu K, Wang FY. Efficacy of magnifying endoscopy with narrow-band imaging in the diagnosis of early gastric cancer and gastric intraepithelial neoplasia. Turk J Gastroenterol. 2024;35(4):299-306.